Characterization of Functionalized Chromatographic Nanoporous Silica Materials by Coupling Water Adsorption and Intrusion with Nuclear Magnetic Resonance Relaxometry - Schlumberger, Carola; Cuadrado Collados, Carlos; Söllner, Jakob; Huber, Christoph; Wisser, Dorothea; Liu, Hsiao Feng; Chang, Chun Kai; Schuster, Stephanie A.; Schure, Mark R.; Hartmann, Martin; Siepmann, J. Ilja; Thommes, Matthias (ACS Applied Nano Materials, 2024)
Nanoporous silica is widely used as a support material for chemically bound stationary phases in chromatographic separations as well as for catalytic applications. Tuning of textural properties and surface chemistry of stationary phase materials (SPMs) is crucial to enhance their selectivity to certain compounds and the resulting process efficiency. Nanoporous silica supports are beneficial, as surface modifications are possible with a large variety of hydrophilic and hydrophobic functional groups, but their influence on the surface properties has not been evaluated in detail. In this sense, the contact angle is a key parameter for the assessment of surface chemistry, but its quantification in pores is challenging and requires a combination of various experimental techniques. This work demonstrates that combining water adsorption and intrusion measurements allows for the determination of the effective contact angle of adsorbed water on the pore walls for wetting, partial wetting, and nonwetting situations using functionalized hydrophilic and hydrophobic silica SPMs as model materials. Furthermore, NMR relaxometry experiments reveal that the ratio of the spin-lattice (T1) to spin-spin (T2) relaxation time of the adsorbed water film (T1,ads.film/T2,ads.film ratio) can be correlated with the effective adsorption strength of water on the surface. Indeed, a linear correlation between the negative inverse relaxation time ratio (−T2,ads.film/T1,ads.film) and the contact angle is observed. Our work demonstrates that water vapor adsorption and water intrusion experiments coupled with NMR relaxometry can be used as complementary tools to quantify the wettability and surface chemistry of nanoporous materials. This approach allows for addressing important aspects of nanoscale wettability in the context of material synthesis as well as for their application in chromatographic separation processes and catalysis.
CRIS-Team Scopus Importer:2024-02-16
Keywords: catalysis; chromatography; nanoporous materials; NMR relaxometry; surface chemistry; water adsorption; water intrusion; wettability

Characterization of functionalized chromatographic silica materials : Coupling water adsorption and intrusion with NMR-relaxometry - Schlumberger, Carola; Cuadrado Collados, Carlos; Söllner, Jakob; Huber, Christoph; Wisser, Dorothea; Liu, Hsiao-Feng; Chang, Chun-Kai; Schuster, Stephanie; Shure, Mark; Hartmann, Martin; Siepmann, Ilja; Thommes, Matthias (ACS Applied Nano Materials, 2023)

Characterization of Hierarchically Ordered Porous Materials by Physisorption and Mercury Porosimetry—A Tutorial Review - Schlumberger, Carola; Thommes, Matthias (Advanced Materials Interfaces, 2021)
This paper is devoted to the textural characterization of nanoporous materials with a focus on hierarchically ordered materials such as mesoporous zeolites, which exhibit an interconnected pore network consisting of micro-, meso-, and often macropores. Hierarchically ordered zeolites have the potential to improve various industrial applications for instance in the areas of heterogeneous catalysis, separation, gas, and energy storage. Detailed insights into the pore architecture are important, because they control transport phenomena, diffusional rates, and govern selectivity, e.g. in catalyzed reactions. However, a reliable characterization of such complex pore structures is still a major challenge. Within this context, the application of advanced physisorption methodologies for micro-mesopore analysis is discussed but also the characterization of macroporosity by mercury porosimetry is addressed. Fundamental concepts and recent major advances in understanding the underlying mechanisms are highlighted. In conjunction with selected case studies, it is illustrated how the application of advanced physisorption methodologies allows i) for the determination of reliable surface areas, pore volumes, and pore size distributions and ii) for obtaining information about pore network characteristics. This tutorial offers guidance for an advanced characterization of nanoporous materials by physisorption and mercury intrusion/extrusion.
CRIS-Team Scopus Importer:2021-02-26
Keywords: hierarchically ordered porous materials; hysteresis; mercury porosimetry; nanopores; physical adsorption; pore size analysis; surface area

Characterization of Nanoporous Materials - Thommes, Matthias; Schlumberger, Carola (Annual Review of Chemical and Biomolecular Engineering, 2021)
Detailed analysis of textural properties, e.g., pore size and connectivity, of nanoporous materials is essential to identify correlations of these properties with the performance of gas storage, separation, and catalysis processes. The advances in developing nanoporous materials with uniform, tailor-made pore structures, including the introduction of hierarchical pore systems, offer huge potential for these applications. Within this context, major progress has been made in understanding the adsorption and phase behavior of confined fluids and consequently in physisorption characterization. This enables reliable pore size, volume, and network connectivity analysis using advanced, high-resolution experimental protocols coupled with advanced methods based on statistical mechanics, such as methods based on density functional theory and molecular simulation. If macropores are present, a combination of adsorption and mercury porosimetry can be useful. Hence, some important recent advances in understanding the mercury intrusion/extrusion mechanism are discussed. Additionally, some promising complementary techniques for characterization of porous materials immersed in a liquid phase are introduced.
CRIS-Team WoS Importer:2021-07-23

Classification and characterization of multimodal nanoparticle size distributions by size-exclusion chromatography - Gromotka, Lukas; Uttinger, Maximilian; Schlumberger, Carola; Thommes, Matthias; Peukert, Wolfgang (Nanoscale, 2022)
Size-exclusion chromatography (SEC) is a well-known, versatile and scalable technique for the separation of molecules according to their hydrodynamic size in solution as well as for the determination of molecular weight distributions of polymers. In this paper we demonstrate and generalize the applicability of SEC to the classification and characterization of multimodal distributions of nanoparticles over a broad size range. After calibration with gold standards from 5 nm to 80 nm, the calibration curve is used to determine the particle size distributions (PSDs) of the standards which are in agreement with comprehensive nanoparticle size analysis by analytical ultracentrifugation. Universal calibration curves independent of the core material and surface functionality can be constructed if the pore diameter of the stationary phase exceeds the particle diameter by a factor of 2-3. Mixtures of gold standards are separated by SEC and evaluated in terms of peak resolution and size-dependent separation curves depending on how well the individual peaks are resolved. Baseline separation of a multimodal mixture is observed and its PSD is determined. Mixtures can be fractionated into coarse and fine fractions with nm precision at different switching times of the fraction collector. Our study demonstrates the strength of SEC to classify multimodal PSDs as well as to accurately determine size distributions of complex nanoparticle dispersions over a broad size range.

Effect of confinement on the characterization of nanoporous materials by NMR relaxometry - Vorndran, Carola; Sandner, Lukas; Schuß, Andreas; Thommes, Matthias (Adsorption-Journal of the International Adsorption Society, 2025)
Valid textural characterization is crucial for many applications such as catalysis, separation as well as energy storage/conversion. In that regard, textural characterization in the gas/dry state using gas physisorption and mercury porosimetry is well established, but these methods might not be sufficient for the characterization of wet materials used in liquid-phase processes. Within this context, the applicability of nuclear magnetic resonance (NMR) relaxometry for surface area assessment of nonporous silica/carbon materials has been demonstrated [Schlumberger et al. (2023). https://doi.org/10.1021/acs.langmuir.2c03337]. However, a comprehensive and rigorous assessment of the applicability of NMR relaxometry for surface area and pore size assessment of nanoporous materials coupled with a systematic investigation of how the confinement affects the NMR relaxation behavior is missing so far. Hence, we present here a systematic study based on a series of ordered mesoporous silica model materials exhibiting well-defined pore sizes between approx. 2.5 and 10 nm saturated with a bulk liquid water as well as a bulk water vapor phase. The study suggests that an adaption of the two-fraction-fast-exchange model to account for the pore geometry is necessary for valid surface area assessment as well as pore size analysis of nanoporous silica material particularly for pores smaller than approx. 10 nm.
CRIS-Team Scopus Importer:2025-05-30
Keywords: Adsorption; Confinement; Nanoporous materials; NMR relaxometry; Pore size analysis; Surface area assessment

From Meso to Macro: Controlling Hierarchical Porosity in Supraparticle Powders - Sultan, Umair; Götz, Alexander; Schlumberger, Carola; Drobek, Dominik; Bleyer, Gudrun; Walter, Teresa; Loewer, Erik; Peuker, Urs Alexander; Thommes, Matthias; Spiecker, Erdmann; Apeleo Zubiri, Benjamin; Inayat, Alexandra; et al. (Small, 2023)
A drying droplet containing colloidal particles can consolidate into a spherical assembly called a supraparticle. Such supraparticles are inherently porous due to the spaces between the constituent primary particles. Here, the emergent, hierarchical porosity in spray-dried supraparticles is tailored via three distinct strategies acting at different length scales. First, mesopores (<10 nm) are introduced via the primary particles. Second, the interstitial pores are tuned from the meso- (35 nm) to the macro scale (250 nm) by controlling the primary particle size. Third, defined macropores (>100 nm) are introduced via templating polymer particles, which can be selectively removed by calcination. Combining all three strategies creates hierarchical supraparticles with fully tailored pore size distributions. Moreover, another level of the hierarchy is added by fabricating supra-supraparticles, using the supraparticles themselves as building blocks, which provide additional pores with micrometer dimensions. The interconnectivity of the pore networks within all supraparticle types is investigated via detailed textural and tomographic analysis. This work provides a versatile toolbox for designing porous materials with precisely tunable, hierarchical porosity from the meso- (3 nm) to the macroscale (≈10 µm) that can be utilized for applications in catalysis, chromatography, or adsorption.
CRIS-Team Scopus Importer:2023-04-07
Keywords: adsorption; hierarchy; porous materials; self-assembly; supraparticles; tomography

Gas separation performance of ultra-permeable graphene oxide membranes supported by single-wall carbon nanotubes: Unveiling the effect of fabrication method, gas flow transport type, and material aging - Gardenӧ, Dániel; Bábanová, Laura; Mazánek, Vlastimil; Sofer, Zdeněk; Kříž, Pavel; Mrazík, Lukáš; Mareš, Jan; Floreková, Jana; Schneider, Josef; Ashtiani, Saeed Jamali; Vorndran, Carola; Thommes, Matthias; et al. (Journal of Membrane Science, 2025)
This study comprehensively investigated the impact of the preparation method on the resulting material properties of self-standing graphene oxide (GO) membranes and GO membranes deposited on a single-walled carbon nanotube (SWCNT) support layer, which was carried out using SEM, XRD, XPS, Raman and FTIR spectroscopy, 3D profilometry, thermal analysis and physisorption characterisation. The analysis of the gas permeability and separation properties of the membranes (including the effect of ageing) performed by repeated time-lag measurements of individual gases revealed a gradually increasing permeability and ideal selectivity, probably due to the release of residual water from the mother liquor. Samples prepared by the evaporation or vacuum filtration method exhibited a relatively short lifetime (up to 100 h), high H2 permeability (up to 12,000 Barrers), and ideal H2/CO2 selectivity from 2 to 3. In contrast, membranes prepared by the pressure filtration method showed durable character for almost 800 days while showing huge and increasing permeability exceeding 100,000 Barrers and, at the same time, remarkable selectivity for H2/CO2 (more than 4) and H2/CH4 (around 2) gas vapors, over the 2008 Robeson upper bound limit. The transport analysis performed via the Binary Friction Model revealed the predominant type of gas transport as Darcy flow rather than Knudsen type. Our work demonstrates the potential of GO-SWCNT membrane materials for developing new advanced separation membranes for future efficient gas, vapor, or liquid separation technologies.
CRIS-Team Scopus Importer:2025-05-09
Keywords: Binary friction model; Darcy; Gas permeability; Gas transport; Graphene oxide membrane; Knudsen; Material aging; Robeson upper bound overcoming

Reliable Surface Area Assessment of Wet and Dry Nonporous and Nanoporous Particles: Nuclear Magnetic Resonance Relaxometry and Gas Physisorption - Schlumberger, Carola; Sandner, Lukas; Michalowski, Alexander; Thommes, Matthias (Langmuir, 2023)
The reliable assessment of surface area is extremely important for many applications, e.g., catalysis, separation, and energy storage/conversion. Within this context, major progress has been made concerning the textural characterization of porous materials in the gas/dry state, e.g., gas physisorption and mercury porosimetry. However, these methods are not sufficient for the characterization of wet materials utilized in liquid-phase processes. For this, the application of nuclear magnetic resonance (NMR) relaxometry has been considered, but a systematic and rigorous assessment of the applicability of NMR relaxometry for reliable surface and pore size characterization of nanoporous materials is missing. Hence, we present a systematic study in which we assess the applicability of NMR relaxometry for reliable surface area assessment utilizing for the first time true surface area benchmark data based on argon 87 K adsorption on nonporous particles (silica and carbon black) coupled with the development of an advanced methodology including the investigation of the choice of the probe molecule and the effect of its accessibility to the pore network. Our results show that the method provides a fast (a few minutes per measurement) and reliable surface area of silica and carbon black model materials immersed in a liquid phase. In addition, our work clearly demonstrates the potential of NMR relaxometry for the targeted surface area assessment of defined pore classes (here ultramicropores) and suggests a new methodology for the characterization of pore entrances (pore window size). Furthermore, we investigate the effect of wettability and suggest that NMR relaxometry could be developed into a unique tool for assessing the wetting characteristics of adsorbate phases on pore surfaces. This fundamental study can be considered a first major step in enabling NMR relaxometry for reliable surface area assessment for wet materials, particularly relevant for materials used in processes occurring in a liquid phase.
CRIS-Team WoS Importer:2023-04-14

Reliable surface area determination of powders and meso/macroporous materials: Small-angle X-ray scattering and gas physisorption - Schlumberger, Carola; Scherdel, Christian; Kriesten, Martin; Leicht, Peter; Keilbach, Andreas; Ehmann, Heike; Kotnik, Petra; Reichenauer, Gudrun; Thommes, Matthias (Microporous and Mesoporous Materials, 2022)
The specific surface area is key for various application fields of porous materials. Its reliable and fast determination is therefore crucial for materials development and product quality management. Surface area assessment is usually based on physical adsorption using the Brunauer-Emmett and Teller (BET) theory. However, the BET method/gas adsorption exhibits a number of limitations and challenges including (i) time consuming sample preparation and measurement time, and (ii) reliable surface areas only possible for non-porous and meso-/macroporous materials to obtain reliable surface areas. In addition, the accuracy of surface area data obtained from adsorption depends on the proper choice of adsorptive/probe. Within this context, this work evaluates in a rigorous way in-depth Small Angle X-ray Scattering (SAXS) as an alternative and complimentary approach for reliable and fast surface area assessment. To our knowledge, this work can be considered the first systematic study where the surface areas from SAXS are compared and validated with true benchmark surface area data. We utilize silica-based nanoparticles as well as a well-defined mesoporous controlled pore glass for systematic SAXS and adsorption studies (argon and nitrogen at 87 K and 77 K, respectively). Owing to the lack of micro- and narrow mesopores of these model materials, the BET method based on argon 87 K adsorption can be applied to determine benchmark surface areas. Indeed, excellent agreement was found between surface areas derived from argon 87 K adsorption and SAXS. In fact, we demonstrate that the determination of specific surface area can be brought with SAXS to a new level, where parameters such as size of the probing adsorptive, its orientation and thus its effective cross-sectional area (when adsorbed on the surface) are no longer affecting the value of the specific surface area determined. Furthermore, SAXS was shown to be significantly faster than gas adsorption. For the silica materials used, the study shows that SAXS does not require degassing and – along with analysis times of only few minutes per sample – provides an accurate and extremely fast, high-throughput approach. This fundamental study can be considered a major step in enabling SAXS for reliable surface area assessment for applications both in nanoporous materials development and quality control, thus boosting SAXS for surface area determination in general, but in particular also for materials, where the usage of gas adsorption is restricted or not possible at all.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Absolute calibration; BET Method; Gas adsorption; Small-angle X-Ray scattering; Specific surface area

Spray Printing of Porous Substrates from Nanosuspensions - Panduro Vela, David; Schlumberger, Carola; Thommes, Matthias; Bück, Andreas (Processes, 2023)
In this work, we present and characterise an experimental setup that allows the generation of porous packings from nanosuspensions. By defined positioning and drying of solid-containing droplets, large-scale porous structures can be generated. Examples of such structures are shown and characterised. Operational challenges are presented, and it is discussed how they can be overcome to allow the maximum degree of freedom in packing generation.
CRIS-Team Scopus Importer:2023-05-12
Keywords: drop-on-demand; drying; porosity; suspension; textural characterization

Study of evolution of three-dimensional porous structure in zeolite-templated carbons - Arsakay, Madi; Shen, Boyuan; Chen, Xiao; Xiong, Hao; Duisenova, Korlan; Fatkhulloev, Alisher; Vorndran, Carola; Yang, Guangwu; Annageldyyev, Bayrammuhammet; Lee, Sun Hwa; Seong, Won Kyung; Thommes, Matthias; et al. (Carbon, 2025)
The atomic-scale and near-atomic-scale local structures during zeolite-templated carbon (ZTC) growth are not well understood. Our study provides insights into the structural evolution from the early to later stages, and finally, the completed stages of growth (i.e., carbon deposition inside the zeolite pores) of Ca-exchanged FAU zeolite-templated carbon using acetylene as a carbon source, through integrated differential phase contrast (iDPC) STEM. We observed that the carbon contrast in the different Ca-FAU channels varies over a wide range at the beginning of the growth (growth times of 10- and 20-min), indicating that different channels have a different number of carbon atoms in this early stage, and that a complete network has not yet been formed. As the time exposure to acetylene is extended (to 60- and 180-min), samples are made that show a high contrast in all channels and carbon atoms are more uniformly distributed (and more uniformly at 180 min than 60 min). Furthermore, the combination of CO2 and Ar adsorption techniques provides a full pore size distribution and provides values for the inner and outer surface areas and volumes of the hollow carbon structure. These findings can help to better understand the structure of ZTCs at the atomic and near-atomic levels, which can be leveraged to enhance ZTC performance in existing applications and potentially enable their use in new applications.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Atomic resolution; Carbon; Gas adsorption; Integrated differential phase contrast scanning transmission electron microscopy (iDPC-STEM); Surface area; Zeolite; Zeolite-templated carbon

Substituting fossil-based with bio-based chemicals: the case of limonene as a greener pore expander for micellar templated silica - Sultan, Umair; Städtke, Katrin; Göpfert, Andreas; Lemmen, Daniel; Metwali, Ezzeldin; Maiti, Santanu; Schlumberger, Carola; Yokosawa, Tadahiro; Apeleo Zubiri, Benjamin; Spiecker, Erdmann; Vogel, Nicolas; Unruh, Tobias; et al. (RSC Sustainability, 2023)
Porous materials are widely used in applications such as adsorption, catalysis and separation. The use of expander molecules is a versatile route to enlarge the mesopore size in micellar templated mesoporous silica materials. Typical expanders used for this purpose are fossil-based organic molecules such as trimethylbenzene (TMB). In the course of making such syntheses greener and more sustainable, it is highly desirable to substitute such fossil-based chemicals with renewable ones. Here, we show that bio-based limonene can be used as an alternative expander molecule for the synthesis of large-pore templated silica. On the basis of electron microscopy, nitrogen physisorption and small angle X-ray scattering we show that the substitution of TMB by limonene leads to very similar material characteristics, reaching mean mesopore diameters of 17-19 nm. A comparative life-cycle assessment demonstrates the reduced environmental impact of limonene production from citrus peel waste compared to TMB production, supporting the call for more applications of renewable chemicals, ideally from waste-streams, also for the production of porous materials.
CRIS-Team Scopus Importer:2023-10-06